2015
DOI: 10.1016/j.memsci.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

A compatible crosslinker for enhancement of CO2 capture of poly(amidoamine) dendrimer-containing polymeric membranes

Abstract: a b s t r a c tPoly(amidoamine) (PAMAM) dendrimers are physically immobilized in a crosslinked poly(ethylene glycol) (PEG) upon photopolymerization of PEG dimethacrylates (PEGDMAs) in the presence of the dendrimers in ethanol. The dendrimer-containing polymeric membranes exhibit excellent CO 2 separation properties over smaller H 2 . However, immiscibility of PEG matrix and the dendrimer results in the formation of a bicontinuous phase-separated structure on a couple of microns scale, which inhibits to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…However, many polymer membranes suffer from a trade-off relationship, i.e., membranes with higher permeability are less selective and vice versa [13]. Thus, it is important to develop advanced polymer membranes with higher permeability as well as higher selectivity [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, many polymer membranes suffer from a trade-off relationship, i.e., membranes with higher permeability are less selective and vice versa [13]. Thus, it is important to develop advanced polymer membranes with higher permeability as well as higher selectivity [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Membranes 2019, 9, 167 2 of 7 membrane for pre-combustion. However, it is very difficult to separate CO 2 over H 2 , because the molecular size of CO 2 is greater than that of H 2 , and only limited numbers of CO 2 selective membranes were reported for this purpose [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that poly(amidoamine) (PAMAM) dendrimer showed excellent CO 2 /N 2 separation performance in a liquid immobilized membrane (ILM) under 200 kPa low pressure [14]. In our group, PAMAM dendrimer/crosslinked-polymer hybrid membranes, such as PAMAM dendrimer/poly(ethylene glycol) (PEG) hybrid membranes [11][12][13] have been developed by immobilizing PAMAM dendrimer into the cross-linked polymer matrix for use in high pressure CO 2 separation. We found that these membranes show high CO 2 /H 2 separation performance at pressurized conditions, and have the potential to be applied for pre-combustion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance CO2 permeance by decreasing membrane thickness, CPC was used to prepare the composite membrane with a thin selectivity layer [10] . The composite membranes, which consisted with PAMAM dendrimer / PEGDMA/CPC hybrid thin layer supported on substrate membrane, were successfully prepared.…”
Section: Introductionmentioning
confidence: 99%